Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/pro.3984
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of tetrathionate hydrolysis based on the crystal structure of tetrathionate hydrolase from Acidithiobacillus ferrooxidans

Abstract: Tetrathionate hydrolase (4THase) plays an important role in dissimilatory sulfur oxidation in the acidophilic iron-and sulfur-oxidizing bacterium Acidithiobacillus ferrooxidans. The structure of recombinant 4THase from A. ferrooxidans (Af-Tth) was determined by X-ray crystallography to a resolution of 1.95 Å. Af-Tth is a homodimer, and its monomer structure exhibits an eight-bladed β-propeller motif. Two insertion loops participate in dimerization, and one loop forms a cavity with the β-propeller region. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Recombinant Af -Tth crystals (hexagonal cylinder with dimensions of 0.2 mm × 0.05 mm × 0.05 mm) have been successfully obtained ( Kanao et al, 2013 ) and the X-ray crystallographic results reported ( Kanao et al, 2021 ). Af -Tth is a homodimer and its monomer structure exhibits an eight-bladed beta-propeller motif, as determined by X-ray crystallography at 1.95 Å resolution.…”
Section: Reaction Mechanism Of Tetrathionate Hydrolysismentioning
confidence: 80%
See 1 more Smart Citation
“…Recombinant Af -Tth crystals (hexagonal cylinder with dimensions of 0.2 mm × 0.05 mm × 0.05 mm) have been successfully obtained ( Kanao et al, 2013 ) and the X-ray crystallographic results reported ( Kanao et al, 2021 ). Af -Tth is a homodimer and its monomer structure exhibits an eight-bladed beta-propeller motif, as determined by X-ray crystallography at 1.95 Å resolution.…”
Section: Reaction Mechanism Of Tetrathionate Hydrolysismentioning
confidence: 80%
“…These results suggest that the sole cysteine residue (Cys301) in Af-Tth is not involved in the tetrathionate hydrolysis reaction or subunit assembly, indicating a novel cysteine-independent reaction mechanism for this enzyme. obtained (Kanao et al, 2013) and the X-ray crystallographic results reported (Kanao et al, 2021). Af-Tth is a homodimer and its monomer structure exhibits an eight-bladed beta-propeller motif, as determined by X-ray crystallography at 1.95 Å resolution.…”
Section: Reactionmentioning
confidence: 89%
“…2 33 , and then a hydrolysis reaction (Eq. 3 shows that for tetrathionate, but the reactions for other S n O 6 2− are analogous) produces S 8 as the most stable end product 34 (S 8 detection by Aponte et al 2023 14 ) [Eq. 3 ]: …”
Section: Discussionmentioning
confidence: 99%
“…This latter enzyme, typical of acidophiles, is a homodimer whose final products and localization (periplasmic or bound to the outer membrane) are still under debate. The structure resolution of the enzyme from Acidithiobacillus ferrooxidans allowed to propose a mechanism for S 0 , S2O3 2and SO4 2generation from the hydrolysis of S4O6 2- (Kanao et al 2021). In phototrophic bacteria, instead, the soluble periplasmic cytochrome c thiosulfate dehydrogenase TsdA catalyses the S2O3 2oxidation to S4O6 2-, transferring electrons either to a dedicated cytochrome c TsdB, encoded upstream, or to a unspecific cytochrome or an HiPIP (see Kurth et al 2016).…”
Section: Sn 2and S 0 Oxidationmentioning
confidence: 99%